Transcriptomic Insights into Differential Gene Expression in Acinetobacter baumannii Isolates from Colistin-Treated Patients Using Illumina Sequencing - Bobbillapati, Janakiram; Latha Jeevigunta, Naveena Lavanya; Girija, AS Smiline (Journal of Neonatal Surgery, 2025)
The rise of multidrug-resistant (MDR) Acinetobacter baumannii presents a critical threat to global health due to its remarkable antibiotic resistance. To explore its stress response mechanisms, RNA sequencing (RNA-seq) was conducted to compare the transcriptomes of A. baumannii ATCC19606 and a clinical isolate from a colistin-treated patient. Analysis identified 118 differentially expressed genes (DEGs) with thresholds of log2 fold change (Log2FC) > 1 or < −1 and FDR < 0.05. Upregulated genes included those encoding twitching motility protein, p-aminobenzoate synthetase, pilin-like competence factor, and D-methionine-binding lipoprotein MetQ, with a 2-4 fold increase. Conversely, downregulated genes, such as ferredoxin, molecular chaperones GroES/GroL, and class C beta-lactamase ADC-158, suggested reduced metabolic activity. These DEGs are implicated in stress response and metabolic transport pathways, providing critical insights into A. baumannii’s adaptive mechanisms and potential vulnerabilities for therapeutic targeting.